If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6 = 11 + 2x Combine like terms: 3 + -6 = -3 -3 = 11 + 2x Solving -3 = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + -2x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + -2x = 11 + 0 -3 + -2x = 11 Add '3' to each side of the equation. -3 + 3 + -2x = 11 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 11 + 3 -2x = 11 + 3 Combine like terms: 11 + 3 = 14 -2x = 14 Divide each side by '-2'. x = -7 Simplifying x = -7
| 10x-5+8x=5(6x-2)+2 | | 7y-21x=7 | | -4=w-3/4 | | 0.6m=-18 | | (x)(x+1)=10x | | 7+9=11(z-8) | | 2x^2+17x-55=0 | | -16t^2+96t+80=124 | | 2/7m-1/3=4/5 | | 20+20+z=-20+5z | | -2y+16=4x | | -16t^2+96t+80=125 | | 28=3(2p-6) | | 7h(11h-8)= | | 3x(2x+20)=180 | | Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 |